Pre-Existing Weather Phenomena for Spreading Dengue Fever Over Dhaka in 2019 - Sultana, Shahanaj; Mannan, Md Abdul; Khan, Md Abdur Rahman; Khandaker, Ronakey; Md Kamrujjaman, - (Journal of Engineering Science, 2020)
An attempt has been made to investigate the outbreak of dengue fever over Dhaka city by examining the preexisting condition of weather elements over Bangladesh. For the study, the maximum temperature, minimum temperature, rainfall, humidity data is analyzed to find the optimum values which trigger the dengue fever over Dhaka city. If the pre-existing weather phenomena are analyzed and compute, it will be possible to settle down which elements are responsible for spreading dengue fever over Dhaka city in 2019. The average minimum and maximum temperature were relatively high in winter season of 2019 than that of the winter of 2018 which may trigger epidemic dengue fever. In June increased temperature and intermittent rainfall (260mm within 17 days) which is also causes of spreading dengue. This is why, Dhaka city, 51,777 dengue cases have occurred from 1st January to 31 December 2019 on the other hand 50,726 dengue cases had occurred during 2000–2018. In the future, due to climate change and its unstable weather phenomena, weak administrator, unplanned urbanization, environmental erosion, and increasing population, dengue risk will be high. If Dhaka city people are not conscious, dengue may increase more upcoming years due to the possibility of increasing temperature, the occurrence of abnormal rainfall, the environmental condition of Dhaka city, and attack trend of previous years. Journal of Engineering Science 11(2), 2020, 99-106